Post‐fire tree establishment and early cohort development in conifer forests of the western Cascades of Oregon, USA. Issue 7 (15th July 2014) - Tepley, Alan J.; Swanson, Frederick J.; Spies, Thomas A.
Abstract : Early‐seral ecosystems make important contributions to regional biodiversity by supporting high abundance and diversity of many plant and animal species that are otherwise rare or absent from closed‐canopy forests. Therefore, the period of post‐fire tree establishment is a key stage in forest stand and ecosystem development that can be viewed in the context of competing management interests in diverse early‐seral ecosystems vs. rapid forest development for ecological or commercial objectives. Previous work in Douglas‐fir/western hemlock forests of the Pacific Northwest suggests stands initiate either with abrupt establishment (<20 years) or by protracted establishment with low tree density persisting >100 years. To improve understanding of how post‐fire tree establishment and early cohort development have varied in space and over time and elucidate some of the factors contributing to that variation, we analyzed forest structure, tree ages, and Douglas‐fir growth across the central western Cascades of Oregon where cohort ages span nearly eight centuries. The number of post‐fire cohorts was estimated per stand, and establishment trajectories were evaluated by cohort. On average, it took 43.5 years to reach establishment of 90% of the trees per cohort. The rate and duration of establishment were surprisingly consistent across variation in topography (elevation, slope position, and aspect), among cohorts initiated from the late 12th to the early 20th century, and regardless of the severity of the cohort‐initiating fire or the timing of establishment by shade‐tolerant species. Only 8% of cohorts completed establishment within 20 years and 12% had establishment lasting >80 years. Douglas‐fir growth (basal area increment) exhibits high plasticity in relation to different competitive interactions within uni‐specific and multi‐species cohorts and between cohorts of different age, suggesting wide variation in the structure and dynamics of early‐seral ecosystems and an ability to tolerate moderate competition when young. This study illustrates that post‐fire establishment in Douglas‐fir/western hemlock forests of the central western Cascades historically was a multi‐decadal process. Limited regeneration in a short window did not necessarily lead to persistent shrublands. In fact, post‐fire forest development appears resilient to considerable variation in the fire regime and climatic and biotic constraints on tree establishment.